Identification of fingerprint image with Minkowski distance algorithm approach - Tulloh, Wisnu Catur Rachmad; Wijayanti, Dian Eka (Bulletin of Applied Mathematics and Mathematics Education, 2023)
In the digital era, fingerprint identification plays a critical role in information technology administration. Various studies have been conducted to improve the fingerprint identification process, but there are still cases of identification failures that are fatal. This research discusses fingerprint identification with the Minkowski distance method. The data of fingerprints are taken from Mathematics students and the Kaggle site. Data analysis includes the steps of image retrieval, dimensioning, conversion to grayscale, pattern matching, and accuracy measurement. Results show an improvement in data accuracy with a structured approach to data capture and preprocessing. Results from primary data obtained an accuracy of 56.67% while from secondary data obtained an accuracy of 93%.